Exploring prospects of floriculture industry in Bangladesh - Khan, Forjana Nasrin; Janakiram, T (Indian Horticulture, 2019)
Floriculture has the potential for further expansion in Bangladesh and has advantage due to its favourable climate, topography, less labour cost and relatively low production cost for growing many flower and ornamental plants which can help the development of flower industry. Although flower production is carried out all over the country, Jessore, Jhenaidah Chuadanga, Dhaka, Cox’s Bazar, Gazipur, Manikganj are the major areas for production. Major constraints in flower production are poor access to quality planting materials, small range of varieties, poor post harvest management, lack of protected cultivation and organized marketing infrastructure, skilled manpower etc. The majority of the floriculture produce in the country is for domestic consumption. Recently, flower has been added into the export item in Bangladesh though it is not remarkable. According to EPB, Bangladesh exported cut flowers and foliage worth 16.58 million during July-November 2013 which exceeded its target by 15.2%. This sector has influenced the national GDP growth as well as employment generation in Bangladesh. To meet the market demand, various flowers, such as chrysanthemum, lilium, carnation, orchids, rose, anthurium are imported from China, India and Thailand every year. Bangladesh spends approximately Tk 2-3 million/year in importing flowers and ornamental plants from abroad. Besides cut flower, foliage and ornamental plants are also potential items for floriculture trade. At present, few avenues for capacity building are being provided by either the government or private sector.